An NSM-based Contrastive Semantic Analysis of Japanese “Nusumu” and “Toru” with Javanese “Nyolong” and “Njupuk” - Santoso, Teguh; Dance, Wamafma; Sawardi, FX; ., Supana; Mulya, Komara; Najmudin, Onin (Journal of Posthumanism, 2025)
In this research, the author aims to discuss the comparison of synonymoue meaning in the verbs nusumu, toru in Japanese and the meaning of the verbs nyolong and njupuk in Javanese. The theory used in this study is the natural semantic metalanguage (NSM) approach (Anna Wiezbicka). The data of the use of nusumu and toru were taken from linguistic corpus data, while that of nyolong and njupuk were gathered from online sources. These four verbs share similar meanings of ’stealing and taking other people’s things to use as your own.’ Based on this analysis, the meanings shared between them include: (1) stealing someone’s belongings secretly so that the owner does not know; (2) stealing or taking other people’s property directly by force; (3) stealing other people’s property by deception; (4) stealing other people’s thoughts or writings (plagiarism); (5) stealing data or digital information; (6) stealing hearts or attention; (7) taking away or limiting the ability to move; (8) taking something to get rid of it; (9) taking choices (chosen study programs at universities, etc.); (10) taking over, representing, picking something up.